Social reproduction, the popular economy and informality: Feminist reflections from Latin America - Luisa Fernanda Tovar Cortés (Cuadernos de Economía, 2022)
The economic discipline is characterised by hierarchical dualisms. This paper examines formal/informal and productive/reproductive binary categories by means of a dialogue between the social reproduction theory and the popular economy. A starting point is the wealth of feminist contributions that highlight both reproduction and work as the heart of socioeconomic phenomena. Based on formalization processes in Latin America, the article explores how public policy interventions focus on the productive sphere. However, upon closer examination, these policies seem to neglect reproductive activities, as well as the demands of popular sectors. We argue that the contributions of feminism are necessary to broaden the economic field.